Religious Practices Position in Firm Performance: A Case of the Malaysian Construction Industry - AHMAD SUFFIAN MOHD ZAHARI; ROSMAN MAHMOOD; ZURIYATI AHMAD; AZZRI FAZRIL ROSMAN (Information Management and Business Review, 2024)
The construction sector is one of the main contributors to a country's economic growth and development. However, the sector is often associated with several issues. Among the factors that cause this failure is related to developer personality characteristics that impact project management efficiency. Therefore, the study's objective is to assess the influence of elements in religious values ??and entrepreneurial factors on the performance of firms in the construction sector. A total of 226 respondents from contractors of various registration grades were used as the study sample. The results of the multiple regression analysis found that the religious factor did not affect the firm's performance. This is linked to the attitude of contractors who often turn their backs on religious values ??and instead use common sense in making decisions and actions. However, all entrepreneurial factors (entrepreneurial competencies, management practice and innovation) show a significant positive influence on firm performance in the construction sector. From a policy perspective, this study highlighted to various stakeholders in the construction industry the existence of laxity in the practice of religious values ??among contractors which is an obstacle to achieving better performance in the implementation of a project. Concerning that, the emphasis on religious values ??needs to be applied thoroughly in every training program in addition to empowering entrepreneurial values ??based on innovation. All of these values ??are important elements in ensuring a firm's sustainable comparative advantage and performance in the construction sector.